2006
DOI: 10.1093/jnci/djj412
|View full text |Cite
|
Sign up to set email alerts
|

Statins, Fibrates, and Melanoma Risk: a Systematic Review and Meta-analysis

Abstract: These findings do not validate the possibility that statins or fibrates prevent melanoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
39
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(47 citation statements)
references
References 56 publications
7
39
0
1
Order By: Relevance
“…Data for incident melanoma cases of four trials [27,28,31,32] were reported in Freeman et al [33]. Regarding the eight fluvastatin RCTs, the number of incident melanoma cases was reported in one summary report [24].…”
Section: Search Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Data for incident melanoma cases of four trials [27,28,31,32] were reported in Freeman et al [33]. Regarding the eight fluvastatin RCTs, the number of incident melanoma cases was reported in one summary report [24].…”
Section: Search Resultsmentioning
confidence: 99%
“…Three previously published meta-analyses have also examined the association between statin use and melanoma risk [33,41,42]. However, in these studies the number of RCTs included in the analysis ranged from 5 [41] to 12 [33], involving up to 39,426 participants [33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Statins were not documented to prevent or affect hematological malignancies (51) , or melanoma (a type of skin malignancy) (52).…”
Section: Evidence Against a Low Cholesterol Being Associated With Cancermentioning
confidence: 99%
“…As the number of incident melanoma cases was low, a specific study to address the role of statins in preventing melanoma would need to be designed, with the required power to provide answers (Freeman et al, 2006).…”
Section: Statinsmentioning
confidence: 99%